Reduced Corneal Sensitivity and Sub-Basal Nerve Density in Long-Term Orthokeratology Lens Wear. Issue 4 (July 2017) - Lum, Edward; Golebiowski, Blanka; Swarbrick, Helen A.
Abstract : Objectives: To investigate changes in corneal sensitivity and nerve morphology in orthokeratology (OK) contact lens wear. Methods: In a cross-sectional study, 54 subjects (aged 18–45 years) were grouped into three categories: nonlens (NL), soft lens (SCL), and OK lens wearers. Corneal sensitivity was measured at the corneal apex and 2.5 mm temporal to the apex using the Cochet–Bonnet aesthesiometer. Corneal nerve morphology was assessed by sampling a 1 mm 2 area of the corneal sub-basal nerve plexus using the Heidelberg Retinal Tomograph with Rostock Corneal Module at the corneal apex and 2.5 mm temporal to the apex. Nerve fiber density (NFD) was calculated by measuring the total length of nerve fibers per square millimeter using Image-Pro Analyser. Comparisons between groups were made using mixed analysis of variance and post hoc paired t tests with Bonferroni correction or the Kruskal–Wallis test and post hoc Mann–Whitney U tests as appropriate. Results: There was a significant difference in corneal sensitivity between the three groups ( P =0.027). Central threshold was significantly higher in the OK than NL group (0.69±0.42 g /mm 2 vs. 0.45±0.12 g /mm 2 ; P =0.048). Mid-peripheral threshold was not different between the three groups ( P >0.05). There was a significant difference in NFD between the three groups ( P <0.001). Central NFD was significantly less in the OK than NL and SCL groups (OK: 17.89±4.42 mm/mm 2, NL: 25.87±5.00 mm/mm 2 ; SCL: 24.52±4.93 mm/mm 2 ; P <0.001). Mid-peripheral NFD was not different between the three groups ( P >0.05). Conclusions: Long-term OK lens wear is associated with a decrease in central corneal sensitivity and NFD. The mechanism underlying refractive change during OK treatment seems to impact both corneal sensitivity and nerve morphology. Abstract : Supplemental Digital Content is Available in the Text.